2009
DOI: 10.1530/eje-09-0422
|View full text |Cite
|
Sign up to set email alerts
|

Lipoatrophy in GH deficient patients treated with a long-acting pegylated GH

Abstract: Objective: Changes observed during adult GH deficiency (GHD) are most often reversed with the administration of recombinant human GH (rhGH). To avoid daily injections, a long-acting GH molecule has been obtained by covalent binding of polyethylene glycol (PEG) with rhGH (PEG-GH), allowing weekly s.c. injections. This study was designed to assess its efficacy and safety, in adult GHD subjects. Design and methods: This was a randomized, double-blind, placebo-controlled, multiple-dose, parallel group study. Subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
3
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 29 publications
0
57
3
1
Order By: Relevance
“…However, 13 out of 105 adults with GHD who were treated with PEG-GH developed lipoatrophy at the injection site after the first injection and all further development was terminated in 2009 [35]. The local-site reactions were independent of either PEG-GH dose or IGF-I levels.…”
Section: Pha-794428mentioning
confidence: 99%
“…However, 13 out of 105 adults with GHD who were treated with PEG-GH developed lipoatrophy at the injection site after the first injection and all further development was terminated in 2009 [35]. The local-site reactions were independent of either PEG-GH dose or IGF-I levels.…”
Section: Pha-794428mentioning
confidence: 99%
“…Conjugation of GH to albumin decreased renal clearance and increased half-life; however, this formulation did not exhibit an improved bioavailability in comparison to rhGH 6 . PEGylated GH demonstrated local injection site lipoatrophy in adults and children, thus raising a safety concern 7 ; an additional study with PEGylated GH demonstrated an inadequate IGF-1 response 8 . Another approach involved the fusion of an unstructured amino acid sequence (XTEN) to hGH in order to reduce its renal clearance (VRS-317) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Bruising and pain at the injection site is associated with other long-acting GH therapies, such as PEGylated GH (Pegvisomant) [22] and Nutropin Depot [23]; the latter is also associated with small erythematous nodules at the injection site [23,24]. Lipoatrophy has been of concern with long-acting GH molecules and has recently been reported with PEGylated GH [25].…”
Section: Table 2 Immunogenicity Results For Gh-lrv2 Gh-lrv3 and Hghmentioning
confidence: 99%